2001
DOI: 10.1007/s004390100564
|View full text |Cite
|
Sign up to set email alerts
|

Germ line insertion of mtDNA at the breakpoint junction of a reciprocal constitutional translocation

Abstract: Constitutional chromosomal translocations are relatively common causes of human morbidity, yet the DNA double-strand break (DSB) repair mechanisms that generate them are incompletely understood. We cloned, sequenced and analyzed the breakpoint junctions of a familial constitutional reciprocal translocation t(9;11)(p24;q23). Within the 10-kb region flanking the breakpoints, chromosome 11 had 25% repeat elements, whereas chromosome 9 had 98% repeats, 95% of which were L1-type LINE elements. The breakpoints occur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
56
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(60 citation statements)
references
References 40 publications
4
56
0
Order By: Relevance
“…Consistent with this view, the de novo chromosomal integration of mtDNA associated with Pallister-Hall syndrome in a patient exposed to Chernobyl radiations may be the consequence of NHEJmediated repair of radiation-induced DSBs (Turner et al 2003). Human mtDNA insertion has also been detected at the breakpoint junction of a reciprocal constitutive translocation (Willett-Brozick et al 2001). Genome sequence analysis of budding yeast (Ricchetti et al 1999), human (Mourier et al 2001;Tourmen et al 2002;Woischnik and Moraes 2002;Ricchetti et al 2004), and various plant species (Richly and Leister 2004) provided more evidence in favor of nuclear genome colonization by mtDNA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with this view, the de novo chromosomal integration of mtDNA associated with Pallister-Hall syndrome in a patient exposed to Chernobyl radiations may be the consequence of NHEJmediated repair of radiation-induced DSBs (Turner et al 2003). Human mtDNA insertion has also been detected at the breakpoint junction of a reciprocal constitutive translocation (Willett-Brozick et al 2001). Genome sequence analysis of budding yeast (Ricchetti et al 1999), human (Mourier et al 2001;Tourmen et al 2002;Woischnik and Moraes 2002;Ricchetti et al 2004), and various plant species (Richly and Leister 2004) provided more evidence in favor of nuclear genome colonization by mtDNA.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, recent studies reported the association of human genetic diseases with de novo insertions of mtDNA in the nuclear genome (Willett-Brozick et al 2001;Borensztajn et al 2002;Turner et al 2003;Goldin et al 2004). Reported cases included a patient exposed to Chernobyl radiation, suggesting that DSB repairdriven chromosomal integration of mtDNA may not occur exclusively under experimental conditions.…”
mentioning
confidence: 99%
“…4 Alternatively, in approximately one cell per thousand, the introduced foreign DNA will integrate into chromosomal DNA (although this figure may vary somewhat depending on cell type). 5,6 This phenomenon is not limited to laboratory transfections as many natural cellular processes, such as integration of DNA from apoptotic bodies, 7 repair of chromosomal lesions by insertion of mitochondrial DNA, 8 or retrotransposition events, give rise to de novo integration of DNA. 9, 10 Thus DNA integration may be seen as an ongoing natural process, which can be harnessed to artificially introduce modifications to a cell's genetic content.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, extrachromosomal DNA can contribute to repair of chromosomal breaks. For example, damaged chromosomes have been found to repair by insertion of mitochondrial DNA (8). Finally, in lower organisms, internal retrotransposition is a common natural occurrence to produce genomic alteration and is widely used in the laboratory study of such organisms (9).…”
mentioning
confidence: 99%